Effectiveness of Ondansetron versus Metoclopramide in Hyperemesis Gravidarum - Chhetry, M; Thakur, A; Basnet, P; Joshi, R; Sangraula, H; Majhi, S; Uprety, D K (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The aim was to evaluate the effectiveness of intravenous ondansetron as compared to intravenous metoclopramide in hyperemesis gravidarum. Methods: Sixty-eight patients with hyperemesis gravidarum were randomized to receive either intravenous ondansetron or intravenous metoclopramide according to randomization group, till they started tolerating orally along with supportive therapy and various treatment parameters were compared. Results: No statistically significant differences were found in the number of doses of intravenous medication used (three doses of ondansetron vs four doses of metoclopramide; p value 0.77), weight changes (ondansetron - 0 kg vs. metoclopramide – 1 kg; p value 0.11) during treatment, duration of intravenous fluids (ondansetron – 24 hours vs. metoclopramide- 24 hours; p value 0.48) in the two groups. The duration of hospital stay of the patients in the two groups was comparable (ondansetron - 3 days vs. metoclopramide - 3 days; p value 0.83). Conclusions: Metoclopramide and ondansetron appear to be equally effective to treat hyperemesis gravidarum. Although this was a prospective randomized controlled study, it had a small sample size and the results should be confirmed in a larger and powered study. DOI:http://dx.doi.org/10.3126/njog.v9i2.11753